Clinico-epidemiological studies on bovine dermatophytosis in and around Bikaner - SINGH, N; J S YADAV, THE LATE; SINGH, A P; SHARMA, S N (The Indian Journal of Animal Sciences, 2013)
Animals (198 : 9 bulls, 90 cows, 50 heifers, 3 bullocks and 46 sucking calves) of either sex, naturally infected with bovinedermatophytosis were studied. The lesions were roughly circular, greyish-white, asbestos-like crusts raised above the skin.They were about 1-3 cm in diameter, and scattered over head, neck, face, eyes, ears, legs, tail and down the flanks on boththe sides. The lesions were initially confinne.d by Wood's lamp test The fungus was identified as Trichophyton verrucosum.Histopathological studies of skin biopsies revealed hyperkeratosis, hyperplasia, disintegration and acanthosis of epidermis,spongiosis and leukocytic infiltration of dermis.